Control Strategy of Master-Slave Manipulator Based on Force Feedback for Decommissioning of Nuclear Facilities. (6th June 2022) - Wang, Jin; Li, Haoyuan; Meng, Fansheng; Ma, Rui; Lai, Quanbin; Li, Jianwu; Duan, Xingguang
Abstract : To improve operation and reduce labor intensity during the process of decommissioning of nuclear facilities, a master-slave manipulation robot system based on force feedback for decommissioning of nuclear facilities is proposed, which is divided into three parts: master hand, wall-through pipe, and slave hand. The structure of master hand is designed according to the human-computer interaction design to add the perception of force information based on position perception. The master-slave manipulation system adopts a force-position hybrid control strategy; the position and force are sent to master and slave hand to discover telepresence operation. Incremental position control method realizes the workspace mapping between the master and the slave manipulator to improve the accuracy of the following performance. The novel zero-length spring compensation is designed to recognize the total gravity compensation of the force feedback device. Finally, the relative experiments have verified the work effectiveness of the master-slave manipulation system.